The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3168/jds.2018-15759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter housing system on hygiene, udder health, frostbite, and rumination of dairy cows

Abstract: The objective of this study was to evaluate the effects of 2 winter (December to April) housing systems on dairy cow hygiene scores, frostbite, teat condition, clinical mastitis, and activity and rumination across 3 winter seasons (2013, 2014, and 2015). Certified-organic cows (n = 268) were randomly assigned to 2 treatments (2 replicates per system): (1) outdoor straw pack (outdoor) or (2) 3-sided compost-bedded pack barn (indoor). Cows calved during 2 seasons (spring or fall) at the University of Minnesota W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Before the initiation of the study, fly counts and fly avoidance behaviors, respiration, and hygiene scoring were agreed upon on site by 5 observers (an experienced animal scientist and the 4 observers that were conducting the visual observations for the study). These definitions were based on previous research studies and the training of the animal scientist (Sjostrom et al, 2019;Perttu et al, 2020). Fly counts on cows were recorded twice during the morning (1000 h) and twice during the evening (1600 h) observations.…”
Section: Behavioral and Biological Measurementsmentioning
confidence: 99%
“…Before the initiation of the study, fly counts and fly avoidance behaviors, respiration, and hygiene scoring were agreed upon on site by 5 observers (an experienced animal scientist and the 4 observers that were conducting the visual observations for the study). These definitions were based on previous research studies and the training of the animal scientist (Sjostrom et al, 2019;Perttu et al, 2020). Fly counts on cows were recorded twice during the morning (1000 h) and twice during the evening (1600 h) observations.…”
Section: Behavioral and Biological Measurementsmentioning
confidence: 99%
“…Despite these potential benefits, our survey results indicate that the adoption of compost bedded packs for lactating cows on organic dairy farms in Vermont is relatively limited and, when used as the only bedding system for lactating cows, was less frequent than we had predicted before this survey. One recent study found improved hygiene and udder health for cows housed outdoors ("outwintered") on straw bedded packs compared with cows housed indoors on compost bedded pack during 3 winters in Minnesota (Sjostrom et al, 2019). In our survey, only 1 farm reported primarily using outdoor housing for lactating cows and returning cows to tiestalls only during inclement weather, although 6 respondents commented that cows had daily outdoor access.…”
Section: Future Housing Trends and Research Priorities For Organic Dairy Farmsmentioning
confidence: 57%
“…Activity was highest for cows grazing BMRSS (Table 5), which was probably due to the physical structure of the plant, as cows must be more active to move about the pasture because of the tall stems and long leaves of the BMRSS. Activity was lowest for cows in CSA (Table 5), which could be due to the cooler air temperatures during October when cows were grazing these CSA pastures, as cooler temperatures maybe be associated with lower activity levels [48].…”
Section: Discussionmentioning
confidence: 99%